Development of Class IV Learning Model Based on Class IV Games Primary school - Buana, Vina Gayu; Kasanah, Siti Uswatun (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
This research is a product development study of the Engklek game-based learning model. This study aims to produce a product that is based on crank-play learning models to develop valid and practical nationalist and mutual cooperation characteristics of students. Products developed to include the syntax of crank-based learning models, equipped with nets of conceptual themes, lesson plans, media, worksheets, and authentic judgments. The stages of product development adopted the Dick & Carrey research and development model. Engklek game-based learning is one of the lessons that integrates crank play in it. This crank game-based learning model can develop the character of students.